Interrogations : inside the minds of the Nazi elite / Richard Overy. - Overy, R. J. (Penguin, 2002)
As Nazi leaders were killed, committed suicide or were captured, it was through the interrogation of the survivors that the Allies began to find the true nature of their enemy. This book includes transcriptions of some of the major interrogations.